Nutrient allocation patterns in different aboveground organs at different reproductive stages of four introduced Calligonum species in a common garden in northwestern China - Liu, Ji-Yuan; Zhang, Xue-Lian; Jin, Xin-Yue; Wang, Meng-Ting; Zhang, Yuan-Yuan; Wang, Xi-Yong (Frontiers in Plant Science, 2024)
Introduction The Calligonum species is a typical shrub with assimilative branches (ABs) in arid regions in Central Asia. The nutrient distribution patterns at different reproductive stages are of great significance for further understanding the ecological adaptation and survival strategies of plants. Methods In the present study, a common garden experiment was employed to avoid interference by environmental heterogeneity. Furthermore, the nitrogen (N), phosphorus (P), and potassium (K) allocation characteristics in the supporting organs (mature branches), photosynthetic organs (ABs), and reproductive organs (flowers and fruits) of Calligonum caput-medusae (CC), Calligonum arborescens (CA), Calligonum rubicundum (CR), and Calligonum klementzii (CK) during the flowering, unripe fruit, and ripe fruit phases were systematically analyzed. Results Aboveground organs were the main factors affecting the variation of N, P, and K concentrations and their stoichiometric ratios, and the reproductive stages were secondary factors affecting N, P, and the P:K ratio and species were secondary factors affecting K and the N:P and N:K ratios. Meanwhile, significant interactions were found for all three of the aforementioned factors. The N and P concentrations in the ABs of the four species were highest during the flowering phase, while the N:P ratio was lowest, which then gradually decreased and increased, respectively, during plant growth. This result supported the growth rate hypothesis, i.e., that the growth rate is highest during the early growth stage. In the growth period, the N, P, and K concentrations in each organ of the four Calligonum species followed the power law, with the allocation rates of N and P being generally higher than K. There were differences among the species as the N−P scaling exponent in the ABs of CR was only 0.256; according to the scaling exponent law, this species was the least stressed and had the strongest environmental adaptability. Overall, the adaptability of the four species could be ranked as CR > CA > CC > CK. In conclusion, there were significant differences in nutrient traits among different aboveground organs, species, and reproductive stages. Discussion The results of this study contribute to a deeper understanding of the nutrient allocation strategies of different Calligonum species and provide scientific evidence for the ex-situ conservation and fixation application of these species.